Antioxidant and Antimicrobial Activities of Wedelia trilobata and Morinda pubescens - Jayakumar, D.; Jhancy Mary, S.; Jaya Santhi, R. (Asian Journal of Chemistry, 2010)
The methanolic extracts of two Indian medicinal plants Wedelia trilobata (Linn.) and Morinda pubescens (Smith) belonging to the families of Astraceae and Rubiaceae were investigated for the antioxidant and antimicrobial activities. 2,2-Diphenyl-1-picrylhydrazyl (DPPH) was used as an in vitro model to evaluate the antioxidant activities of different parts of the plants like root, stem, leaves, flower and fruit and it was compared with standard antioxidant L-ascorbic acid. Agar diffusion method was used to study the antibacterial activity against seven bacterial strains in Nutrient-Agar media. In Wedelia trilobata, flower had showed the highest antioxidant activity (99.12 %) at 800 μg when compared to other parts of the plant and exhibited reasonable good antibacterial activity and the inhibition was maximum for Salmonella paratyphi and Bacillus cereus. The antioxidant activities of all the parts of Morinda pubescens were minimum and the root had exhibited highest antibacterial activity against Shigella sonnei with the zone of growth inhibition 26 mm at 25 mg.